Volume kinetic evaluation of fluid turnover after oral intake of tap water, lemonade and saline in volunteers - Zdolsek, Joachim (BMC Sports Sci Med Rehabil, 2016)
BACKGROUND: Volume kinetic fluid turnover of three beverages was investigated for the purpose of estimating their rates of absorption and elimination as well as their maximum effect on the blood volume. The results were then used to simulate the effects of ingesting different combinations of these fluids. METHOD: Ten healthy volunteers ingested 0.5 L of tap water, lemonade (90 g/L carbohydrates) and isotonic saline (9 g/L) on different occasions. Venous blood samples for measurement of the blood haemoglobin (Hb), haematocrit and glucose concentrations were collected on 10 occasions over 2 h. A kinetic model based on haemoglobin dilution and urinary excretion was used to estimate the rate of absorption, the blood volume expansion over time, and the rate of elimination. Obtained kinetic data was used to simulate combinations of the three beverages in order to reach a predetermined goal of a 1:1 hydration of the blood volume and peripheral tissues over 6 h. RESULTS: Tap water had the fastest absorption but primarily hydrated peripheral tissues. Maximum hydration was reached after 17 min. Lemonade effectively expanded the blood volume and was absorbed and excreted at a high rate. The maximum hydration from isotonic saline occurred 60 min after ingestion. Slow excretion could make it possible to use saline to prolong the effects of the other two beverages. CONCLUSIONS: It is possible to use the kinetic model to evaluate fluid turnover and compartmental distribution. Composition and timing of fluid intake can be calculated mathematically to meet predetermined goals of hydration and distribution. TRIAL REGISTRATION: NCT01360333 Date of registration: 05/23/2011. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13102-016-0045-x) contains supplementary material, which is available to authorized users.